Problems and Complexities in Rural Schools of the Himalayan Region: Challenges for Community Development - Panda, S.K.; Singh, Ravail (Journal of Extension Education, 2024)
The educational system of rural areas in India especially in the Himalayan region, is facing various problems like infrastructure, transportation, communication, and quality education. In the present paper, the focus has been given to identifying the problems and challenges faced by rural schools and factors affecting the quality of education in Himalayan region with particular reference to the Paddar sub-division in Jammu and Kashmir Union Territory. Using purposive sampling technique, data were collected from 19 schools, with 180 students as a sample. The findings of the study revealed that low educational qualifications of both parents, low socioeconomic status and low occupational status of parents were the major factors affecting the quality of education. Natural obstacles like harsh winters, heavy snowfall, a high mountainous area, and a lack of transportation also hinder the progress of education. Hence, there is a need to bring structural changes in the rural schools of Jammu & Kashmir.